The mysterious disappearance of Leon (I mean Noel) - Raskin, Ellen (New York : Puffin Books, 2011)
The disappearance of her husband is only the first of the mysteries Mrs. Carillon must solve.
Originally published: New York : Dutton, c1971.
Keywords: Detective and mystery stories; Humorous stories